Revenue forecasting practices : differences across countries and consequences for forecasting performance - Thiess Buettner; Björn Kauder (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper reviews the practice and performance of revenue forecasting in selected OECD countries. While the mean forecast errors are small in most countries, the precision of the forecasts measured by the standard deviation of the forecast error differs substantially across countries. Based on a comparison of forecasting practices we show that these differences can be attributed to a large part to differences in the timing of the forecasts and in the tax structure. In addition, we find some evidence that differences in methods and institutions also matter for the forecasting precision. In particular, we find that the use of macroeconomic models as well as the independence of revenue forecasting are associated with a lower standard deviation of the forecast error.
Keywords: H68; H11; 330; revenue forecasting; international comparison; OECD countries; forecast error; Steuerschätzung; Öffentliche Einnahmen; Prognoseverfahren; Statistischer Fehler; Vergleich; OECD-Staaten